Dynamics of Vegetation Cover by NDVI in the Condebamba Valley, Cajamarca, 2003 – 2024 - Barboza Estela, Willy Overly; Rojas Gonzales, Verónica Judith; Gastolomendo Malimba, Edilberto; Licapa Redolfo, Gladys Sandi (LACCEI, 2025)
The purpose of this study is to evaluate the dynamics of vegetation cover using NDVI in the Condebamba Valley, Cajamarca, between 2003 and 2024. The results record variations in vegetation cover: the maximum NDVI has increased, reflecting improvements in certain areas due to plant conservation and regeneration strategies, while the minimum NDVI has decreased significantly, indicating greater soil degradation due to deforestation, urbanization, mining and the reduction of water resources as a result of climate change. The average NDVI went from 0.245 in 2003 to 0.257 in 2024, showing loss of vegetation. In 2024, the maximum NDVI reached 0.615 and the minimum was recorded in 2028 (- 0.131) and then dropped to -0.102 in 2024, reflecting a fragmentation of the natural landscape with a slow recovery of vegetation cover. Although some areas show signs of restoration, other areas continue to deteriorate. Urban expansion, changes in land use, the existence of mining in the area and climate change have influenced this process. It is recommended to strengthen conservation and reforestation strategies to mitigate these effects.